Anthropometric Assessment for Ergonomic School Furniture Design to Prevent Student Discomfort and Musculoskeletal Disorders - Abiola, Oluranti; Olasunkanmi-Ojo, Mariam; Yusuf, Lukman; Oke, Adekola; Oladejo, Kolawole (Journal of Advanced Industrial Technology and Application, 2026)
Classroom furniture plays a critical role in shaping the comfort, posture, and academic performance of students. However, a widespread mismatch between school furniture dimensions and students’ anthropometric characteristics often results in discomfort and musculoskeletal disorders (MSDs). This study aims to assess the anthropometric measurements of primary and secondary school students in Osun State, Nigeria, to recommend ergonomically appropriate classroom furniture dimensions. Anthropometric data were collected from 900 students (124 in primary and 776 in secondary schools), equally divided by gender and ranging in age from 6 to 20 years. Measurements included sitting height, elbow height, shoulder height, popliteal height, buttock-popliteal length, and other key dimensions, using a standard anthropometer. Existing classroom furniture dimensions were also recorded. Using Microsoft Excel 365, percentiles (5th, 50th, and 95th) were computed to determine appropriate design values. The analysis revealed significant mismatches between current furniture and students' body dimensions, contributing to poor posture and discomfort. Design recommendations were developed for seat and desk dimensions tailored to both primary and secondary students. For instance, the ideal seat height is 28.35 cm for primary and 37.55 cm for secondary students, while desk surface heights range from 42.80–45.61 cm and 50.73–54.87 cm, respectively. The study concludes that incorporating anthropometric data into classroom furniture design can significantly reduce student discomfort and prevent long-term musculoskeletal issues. It emphasizes the urgent need for region-specific ergonomic standards to ensure student well-being and enhance academic productivity.